CLASSIFICATION OF THE IMAGE OF THE MOTHER IN WILLIAM FOLKER'S AS I LAY DYING AND OTKIR HASHIMOV'S WORK OF THE WORLD (Proceedings of International Educators Conference, 2024)
In this article, the portrayal of the mother in Dying and The World's Work can be described in a subtle and thought-provoking way that reflects the authors' unique views on motherhood, family dynamics, and the human experience. As we begin to explore the mother figure in these novels, we are invited to uncover the layers of complexity, emotion, and significance that mothers bring to the stories they inhabit. Mothers in "Death" and "The Work of the World" are ready to leave an unforgettable impression on readers by forming characters, plots and themes of charming literary works, from nurturing and selfless figures to symbols of strength and perseverance.